Investigation of the temperature dependence of single molecule biomolecular interactions - Lone, Mudasir (2008)
Weak non-covalent interactions such as hydrogen bonds, van der Waals forces and hydrophobic interactions form the basis of biomolecular interactions, and hence govern the function of many biological processes such as ligand-receptor interactions (cell adhesion), DNA replication and transcription. Measurement of such forces is important as it enables an understanding of the physio-biochemical properties of biological macromolecules. Single molecule forces and interactions can be measured with the help of ultra high sensitive force measurement devices such as the atomic force microscope (AFM), magnetic tweezers (MT), optical tweezers (OT) and the bio-membrane force probe (BFP). In this study, AFM has been employed over a range of temperatures to study the forced unbinding of streptavidin-biotin and complementary DNA oligonucleotides (30mer). With regards to the DNA based experiments, recently developed dendron immobilization chemistry was employed with the aim of improving sample immobilization and hence force spectroscopy data. At room temperature, the dynamic force spectroscopic measurements of the streptavidin-biotin complex showed two regimes of strength, consistent with previous studies. The unbinding strength of complementary DNA oligonucleotides immobilized via the dendron approach was also investigated at room temperature and found to be consistent with previous studies.